Southern Ocean frontal structure and sea-ice formation rates revealed by elephant seals - Charrassin, J.-B.; Hindell, M.; Rintoul, S. R.; Roquet, F.; Sokolov, S.; Biuw, M.; Costa, D.; Boehme, L.; Lovell, P.; Coleman, R.; Timmermann, R.; Meijers, A.; et al. (Proceedings of the National Academy of Sciences, 2008)
Polar regions are particularly sensitive to climate change, with the potential for significant feedbacks between ocean circulation, sea ice, and the ocean carbon cycle. However, the difficulty in obtaining in situ data means that our ability to detect and interpret change is very limited, especially in the Southern Ocean, where the ocean beneath the sea ice remains almost entirely unobserved and the rate of sea-ice formation is poorly known. Here, we show that southern elephant seals (Mirounga leonina) equipped with oceanographic sensors can measure ocean structure and water mass changes in regions and seasons rarely observed with traditional oceanographic platforms. In particular, seals provided a 30-fold increase in hydrographic profiles from the sea-ice zone, allowing the major fronts to be mapped south of 60°S and sea-ice formation rates to be inferred from changes in upper ocean salinity. Sea-ice production rates peaked in early winter (April?May) during the rapid northward expansion of the pack ice and declined by a factor of 2 to 3 between May and August, in agreement with a three-dimensional coupled ocean?sea-ice model. By measuring the high-latitude ocean during winter, elephant seals fill a ?blind spot? in our sampling coverage, enabling the establishment of a truly global ocean-observing system.
Keywords: Sørishavet; havis; hydrografi; klimaendringer; marin biologi; oseanografi; polarområdene; sjøelefanter; sjøis; sjøpattedyr

Klimagåten Antarktis - Winther, Jan-Gunnar (Gyldendal, 2008)
Keywords: Antarktis; IPY; Sydpolen; ekspedisjoner; internasjonale polarår; isbreer; klimaendringer; klimatologi; polarforskning

Norge i Antarktis : fra erobring til moderne forskning - Winther, Jan-Gunnar; Andersen, Rolf Trolle; Basberg, Bjørn L; Bomann-Larsen, Tor; Haugland, Jan Erling; Njåstad, Birgit; Orheim, Olav; Tveraa, Torkild; Monsen, Oddbjørn (Schibsted, 2008)
Keywords: Antarktis; Norge; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene

Norway in the Antarctic : from conquest to modern science - Winther, Jan-Gunnar; Tveraabak, Jacob; Andersen, Rolf Trolle; Basberg, Bjørn L; Bomann-Larsen, Tor; Haugland, Jan Erling; Njåstad, Birgit; Orheim, Olav; Monsen, Oddbjørn; Goldman, Helle V (Schibsted, 2008)
Keywords: Antarktis; Norge; ekspedisjoner; forskningsstasjoner; forvaltning; hvalfangst; klima; klimaendringer; miljø; naturressursforvaltning; naturvitenskapelig; polarforskning; polarområdene